Identification and Three-dimensional Structural Analysis of Nine Novel Mutations in Patients with Prothrombin Deficiency - Akhavan, Sepideh; Mannucci, Pier M.; Lak, Manijeh; Mancuso, Giacomo; Mazzucconi, Maria G.; Rocino, Angiola; Jenkins, P. Vincent; Perkins, Stephen J. (Thrombosis and Haemostasis, 2000)
Prothrombin deficiency is an autosomal recessive disorder associated with a moderately severe bleeding tendency. In this study, 13 patients with prothrombin deficiency were screened for the presence of alterations in the prothrombin gene, and nine novel candidate mutations were identified. Of 11 patients with hypoprothrombinemia, ten are homozygous for five mutations and one patient is a compound heterozygote. The two patients with dysprothrombinemia are homozygous for two mutations. Eight of nine mutations are missense ones associated with single amino acid substitutions in the propeptide (Arg-1Gln, Arg-2Trp), the kringle-1 (Asp118Try) and kringle-2 (Arg220Cys) domains and the catalytic serine protease domain (Gly330Ser, Ser354Arg, Arg382His and Arg538Cys). The ninth mutation is an in-frame deletion of 3 bp that results in the omission of one amino acid (del Lys 301/302). The combination of these missense mutations with crystal structures for α-thrombin and the prothrombin fragments 1 and 2 resulted in new insight into the function of α-thrombin. The hypoprothrombinemia mutations were inferred to affect either the cleavage of the propeptide from the Gla domain, the stability of the kringle-1 and −2 domains, or the close association of the A and B chains of the serine protease domain. The dysprothrombinemia mutations were inferred to directly affect catalytic function through their location at the active site crevice or exosite 1 within the serine protease domain.
Keywords: Prothrombin deficiency; dysprothrombinemia; hypoprothrombinemia; prothrombin